Response to Ebola vaccine and factors associated with the variability in African countries - (:unkn) unknown (My University, 2023)
The 2014 epidemic of Ebola Virus Disease (EVD) in West Africa was by far the most important Ebola outbreak ever seen, causing about 28,616 cases and 11,310 fatalities. The heterologous two-dose Ad26.ZEBOV, MVA-BN-Filo vaccine regimen against Ebola virus disease was evaluated in several clinical trials worldwide. Although, the results constantly showed that the vaccine is immunogenic, geographic variabilities of the immune response have been found and are yet to be explained. Recurrent exposure to parasites (protozoa and helminths) may play a role in immune response reduction in some endemic African countries, but there is still limited scientific evidence that exposure to helminths infections can have an impact on either the immediate response to vaccination or the durability of the response. There are no data yet in this particular case of the Ebola vaccines, even though it is mainly intended for populations living in areas endemic for helminth infections. The objective of this thesis is to assess the vaccine responses to the Ad26-ZEBOV, MVA-BN-Filo Ebola vaccines regimen and to evaluate its variability. Through phase 2 randomized controlled trials in Europe (EBL2001) and Africa (EBL2002 and EBL3001) conducted from 2015 to 2019, in the framework of a public-private partnership with Janssen infectious disease (IMI2 project EBOVAC2) we evaluated the immune response and safety of the Ad26-ZEBOV, MVA-BN-Filo vaccines in adults as well as in children and adolescents. We found that the vaccine is safe and immunogenic. No vaccine-related SAEs were found and AEs were mainly mild-to-moderate among the participants. In the healthy adult’s cohort, at twenty-one days post-MVA-BN-Filo vaccination, the geometric mean concentrations (GMCs) with 95% confidence intervals (CIs) of EBOV GP binding antibodies, in 28-, 56-, and 84-day interval groups were 3,085 EU/mL (2,648 to 3,594), 7,518 EU/mL (6,468 to 8,740), and 7,300 EU/mL (5,116 to 10,417), respectively. Antibod
Keywords: African Research